Marginalisation of 'global South' epistemics: the case of a soil science textbook - Milton Milaras; Tracey McKay (University of Johannesburg, 2019)
Scientific textbooks are often seen as critical teaching and learning tools for undergraduate students. Furthermore, textbooks can shape and define students' comprehension and internalisation of academic disciplines. Despite this, textbooks are not necessarily error free. Additionally, textbooks can be laden with hidden representational presumptions and biases, foregrounding a particular culture, knowledge system, or hegemonic world-view. This can include the epistemology of the 'global North'. How appropriate it is to prescribe such textbooks in the 'global South' is, therefore, debatable. Thus, this research represents an attempt to determine the suitability of a soil science textbook - produced in the global North - for use in the global South, specifically the South African context. Accordingly, one particular textbook, in use at some South African universities, was analysed using textual analysis, in order to ascertain its applicability within the context of an Africanised curriculum. The study found that, despite the publisher's claim of 'universality', the book presents soil science knowledge as written with a northern geographical setting in mind and for a Western European or North American audience. Thus, for South Africa, with its radically different geographical, cultural, and soil conditions, the textbook is inappropriate and may even be moulding a particular global North worldview. On this basis it is recommended that academics of the global South adopt a critical approach when selecting textbooks; as well as actively promote and write textbooks directly suited to an African setting. How to cite this article: MILARAS, Milton; MCKAY, Tracey. Marginalisation of 'global South' epistemics: the case of a soil science textbook. Scholarship of Teaching and Learning in the South. v. 3, n. 2, p. 31-48. Sept. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=93&path%5B%5D=45 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/